2014
DOI: 10.1007/s40692-014-0025-7
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood teachers’ perceived barriers to ICT integration in teaching: a survey study in Mainland China

Abstract: This paper looked at the barriers to ICT integration in teaching practices from the perspective of Chinese early childhood teachers in Mainland China. A total of 46 Chinese early childhood teachers in Mainland China participated in this study. They were from three early childhood settings located in three different cities in terms of the administrative division. A self-designed questionnaire was adopted as the research instrument. It was found that a range of first-order barriers, which included lack of hardwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 14 publications
1
25
1
1
Order By: Relevance
“…By majority, the above findings are consistent with those of Liu and Pange (2015), and of Nikolopoulou and Gialamas (2015), who observed the negative impact of the meager material and technical infrastructure and technical assistance, plus the non-manageable student responsiveness, in conjunction with the inadequate adoption of the pertinent pedagogical models, on the schoolteacher practices germane to the educational implementation of ICT. Besides, the increase and the equitable distribution of the provided school budget and the melioration of the collegial collaboration, along with the undergraduate and the in-service teacher training, were identified by Goktas, Gedik, and Baydas (2013) as significant prerequisites to the pedagogical inclusion of new technological means.…”
Section: Discussionsupporting
confidence: 85%
“…By majority, the above findings are consistent with those of Liu and Pange (2015), and of Nikolopoulou and Gialamas (2015), who observed the negative impact of the meager material and technical infrastructure and technical assistance, plus the non-manageable student responsiveness, in conjunction with the inadequate adoption of the pertinent pedagogical models, on the schoolteacher practices germane to the educational implementation of ICT. Besides, the increase and the equitable distribution of the provided school budget and the melioration of the collegial collaboration, along with the undergraduate and the in-service teacher training, were identified by Goktas, Gedik, and Baydas (2013) as significant prerequisites to the pedagogical inclusion of new technological means.…”
Section: Discussionsupporting
confidence: 85%
“…Since 1980, the development of information and communication technology (ICT) and the increasing of people's awareness of the value of integrating ICT in education, a number of countries have carried out many initiatives to introduce ICT in their educational systems (Goktas, et al, 2013;Liu & Pang, 2014). Many studies have been conducted on implementation of ICT in in different educational contexts (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The result of observation also showed that the teachers encountered infrastructural problems in using ICT tools in teaching and learning process. The main barriers in integrating ICT into teaching practices perceived by the teacher were lack of pedagogical models, lack of material and content of teaching, and lack of infrastructure such as computers, laptops, and notebooks (Liu, et al, 2015). In this case, this study and the previous study conducted by Liu, et al shows that the teacher encountered infrastructural problems, but the difference is this study shows the infrastructural problem faced was limited number of LCD projector and lack of maintenance of LCD projector in the classroom.…”
Section: Infrastructural Problemsmentioning
confidence: 99%